The Rise and Fall of Public College-Private Partnerships in Ontario - Gill, Seerat; Buckner, Elizabeth; Jones, Glen A. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
In the early 2000s, several northern and rural Ontario public colleges entered contractual agreements that were later termed “public college-private partnerships” (PCPPs). In this model, colleges subcontracted program delivery to private third parties, which primarily educated international students on private campuses, often in the Greater Toronto Area (GTA). This article traces the evolution of PCPPs from 2005 to 2024, using agency theory to analyze relationships between government, public colleges, and private affiliates. While PCPPs allowed colleges to cross-subsidize their public mandate, a practice that financially benefited government and public colleges, we argue that a lack of adequate oversight created agency problems that led to moral hazard and opportunism and, ultimately, contributed to the federal government’s 2024 reforms to international student policies. These reforms led to the near elimination of demand for PCPPs, the winding down of PCPP operations, and had major consequences for the financial stability of Ontario’s public colleges.